Enzim Transferase dengan Bilirubin Total Penderita Ikterus Obstruktif - Fatima Maulidina Fajrian (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Post-hepatic obstructive jaundice is jaundice that caused by an obstruction in the bile ducts that leads to disruption of bile flow between the liver and duodenum. The function of the liver can be measured by examining the activity of serum aminotransferase, known as Serum Glutamic Oxaloacetic Transaminase and Serum Glutamic Pyruvic Transaminase. SGOT, SGPT, and bilirubin is one of the liver productions in which if liver damage occurs, there will be abnormalities in the results. The purpose of this study was to determine the relationship between transferase enzymes and total bilirubin in obstructive jaundice patients. This study was an Observational analytic approach with a cross-sectional design, and the sampling technique was purposive sampling and obtained a sample of 40 people. Patients data were obtained from secondary data with medical records. The bivariate test is done by Spearman’s correlation test. The result showed that there is a good correlation between SGOT levels and total bilirubin levels (p-value = 0.001), with a correlation value of 0.498, also SGPT levels and total bilirubin levels (p-value = 0.011), with a correlation value of 0.397. The conclusion is an increase of total bilirubin levels in obstructive jaundice patients will be accompanied by an increase of SGOT and SGPT levels